1992
DOI: 10.1182/blood.v79.7.1720.bloodjournal7971720
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant and fibrinolytic activities are promoted, not retarded, in vivo after thrombin generation in the presence of a monoclonal antibody that inhibits activation of protein C

Abstract: This study examines the assumption that both the anticoagulant and fibrinolytic activity that follow the generation of thrombin induced by infusion of factor Xa/PCPS are due to generation of activated protein C. Untreated controls or animals given unrelated antibody were compared with animals pretreated with a specific monoclonal antibody to protein C (HPC4). Compared with untreated controls excess HPC4 substantially reduced the level of protein C activation as observed by protein C immunoblotting and enzyme-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Baboon model of E coli sepsis and FXa/PCPS infusion Plasma samples were derived from studies approved by the Institutional Animal Care and Use Committee of the Oklahoma Medical Research Foundation. Papio anubis baboons were IV infused with a single bolus of FXa/PCPS (36.6 pmol/kg body weight FXa and 56.3 nmol/kg body weight PCPS) 9 or LD100 E coli (1 3 10 10 colony-forming units [CFUs]/kg to 3 3 10 10 CFU/kg). 11,15 Baboon blood samples and physiological parameters were collected before (T0) and at the indicated times after challenge with FXa/PCPS or E coli.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baboon model of E coli sepsis and FXa/PCPS infusion Plasma samples were derived from studies approved by the Institutional Animal Care and Use Committee of the Oklahoma Medical Research Foundation. Papio anubis baboons were IV infused with a single bolus of FXa/PCPS (36.6 pmol/kg body weight FXa and 56.3 nmol/kg body weight PCPS) 9 or LD100 E coli (1 3 10 10 colony-forming units [CFUs]/kg to 3 3 10 10 CFU/kg). 11,15 Baboon blood samples and physiological parameters were collected before (T0) and at the indicated times after challenge with FXa/PCPS or E coli.…”
Section: Methodsmentioning
confidence: 99%
“…To test the in vivo role of thrombin and plasmin on complement activation in primates, we used plasma samples from baboons infused with factor Xa (FXa) and phosphatidylcholine-phosphatidylserine (PCPS) vesicles (FXa/PCPS) that trigger a robust burst of thrombin and subsequent plasmin generation in vivo. 8,9 For comparison, we used plasma from baboons infused with LD100 Escherichia coli 10 that leads to activation of the complement, 11,12 coagulation, and fibrinolytic systems. 13,14 We found that bacteria and lipopolysaccharide (LPS) were the main activators of the complement system in E coli sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…For lipopolysaccharide (LPS) challenge, mice were injected intraperitoneally with 40 mg kg )1 LPS from E. coli O127: B8 (Sigma, St. Louis, MO, USA). Factor Xa/phosphatidylcholine (80%) phosphatidylserine (20%) (PCPS) vesicles were prepared as previous described [10]. Two doses of factor Xa/PCPS were used: the low dose was 23.5 pmol kg )1 factor Xa and 36.1 nmol kg )1 PCPS, and the high dose was 70.4 pmol kg )1 factor Xa and 108.3 nmol kg )1 PCPS.…”
Section: Hematological Analysis Of Murine Bloodmentioning
confidence: 99%
“…One example of disease-specific tailoring of DIC is the significantly more intense coagulant response in early trauma. Together with the extensiveness of endothelial cell activation, the excessive surge in thrombin leads to overdrive of tPA-triggered fibrinolysis and indiscriminate fibrin(ogen)olysis, as observed in a baboon model of DIC following blockade of the PC anticoagulant pathway to enhance thrombin generation [ 11 ].…”
Section: Pathophysiological Considerationsmentioning
confidence: 99%